HUBUNGAN TINGKAT KECEMASAN DAN INTENSITAS NYERI HAID DENGAN KONSENTRASI BELAJAR REMAJA PUTRI - Juliyanti, Vera Maifita (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Background: Menstruation is a natural process every month for women, one of the disturbances in the menstrual cycle is the appearance of menstrual pain (dysmenorrhea) and can cause anxiety, pain intensity affects menstrual anxiety. Menstrual pain (dysmenorrhea) and anxiety can interfere with learning and concentration. The purpose of this study was to determine the relationship between the level of anxiety and the intensity of menstrual pain with the study concentration of young women in the nursing program at Widya Husada University, Semarang. Method: This type of research uses a quantitative method and a cross-sectional analytic approach. The research instrument used three instruments, namely the level of anxiety, the intensity of menstrual pain and also the ability to concentrate on learning which had been tested for validity and reliability by other researchers. The sample of this research is 50 respondents. Result: Result of p-value = 0.000 and rho-value = 0.778, Ha is accepted. This shows that there is a relationship between the level of anxiety and the intensity of menstrual pain in young women with a p-value = 0.000 and an rho value of 0.529 which means that Ha is accepted and there is a relationship between the level of menstrual pain. anxiety and learning disabilities of young girls with strong intimacy. Conclusion: Ha is accepted and H0 is rejected, which means there is a relationship between the level of anxiety and the intensity of menstrual pain with the concentration of adolescents studying at Widya Husada University, Semarang.